Персональные компьютеры - Чоговадзе Гоча Георгиевич (Финансы и статистика, 1989)
Экземпляры: КХ (20090225) / Инвентарный номер: 931526 / Цена: 0.80 / Сис.шифр: 32.973 / Авт.знак: Ч-75 / ГРНТИ: 50 / ББК: 32.973.2